2016
DOI: 10.1371/journal.pone.0167880
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Miconazole Nitrate Mucoadhesive Tablets versus Itraconazole Capsules in the Treatment of Oral Candidiasis: An Open-Label, Randomized, Multicenter Trial

Abstract: BackgroundOral candidiasis (OC) is a common oral fungal infection. Recently, miconazole mucoadhesive tablets have been gaining attention for OC treatment. Despite trials in patients with human immunodeficiency virus and cancer, evidence of its application in the large-scale, general population with OC is lacking. This study aimed to evaluate the efficacy and safety of miconazole nitrate mucoadhesive tablets in comparison with itraconazole capsules for OC treatment.MethodsThe study was a randomized, open-label,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Comparing the efficacy and safety of miconazole nitrate tablets and itraconazole capsules in patients diagnosed with oral candidiasis, Yan et al (2016) found a cure rate of 51.18% for miconazole and 41.76% for itraconazole. They also observed no significant differences between these drugs regarding the safety profile of the patients [ 66 ]. Evaluating mucoadhesive tablets of nystatin in healthy volunteers, Llabot et al (2009) found that the tablets resided in the mucosa of the patients for 4.5 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the efficacy and safety of miconazole nitrate tablets and itraconazole capsules in patients diagnosed with oral candidiasis, Yan et al (2016) found a cure rate of 51.18% for miconazole and 41.76% for itraconazole. They also observed no significant differences between these drugs regarding the safety profile of the patients [ 66 ]. Evaluating mucoadhesive tablets of nystatin in healthy volunteers, Llabot et al (2009) found that the tablets resided in the mucosa of the patients for 4.5 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Fluconazole and clotrimazole are the two commonly used anti-fungal agents for the treatment of fungal lesions. [ 9 10 11 ] Hence, we aimed to evaluate the effectiveness of fluconazole and clotrimazole in the treatment of patients suffering from candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that econazole and miconazole dramatically inhibited the tumorigenesis of gastric cancer cells and may potentially serve as powerful anticancer drugs. Miconazole had a better inhibitory effect on cell viability but is known to cause adverse side-effects such as dizziness, hypoesthesia, and decrease white blood cell count (Yan et al, 2016). Therefore, miconazole was not tested in detail in this paper.…”
Section: Econazole Inhibits the Viability Of Several Cancer Cell Lines And Induces Apoptosis Of Gastric Cancer Cellsmentioning
confidence: 99%